2023
DOI: 10.1039/d3re00058c
|View full text |Cite
|
Sign up to set email alerts
|

A 3D printable synthetic hydrogel as an immobilization matrix for continuous synthesis with fungal peroxygenases

Abstract: Enzyme immobilization is the key to an intensified bioprocess that allows recycling of the heterogenized enzyme and/or continuous biocatalytic production. In this communication, we present a case study for enzyme...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Beyond medical applications, these 3D printable hydrogels could also be suitable as enzyme carriers in biocatalysis, as they provide a suitable aqueous microenvironment for the enzyme and the surface is designable via 3D printing. 19,54 Furthermore, these hydrogels could be useful as ion exchangers or absorbers for downstream processing, wastewater treatment, or chromatography. [55][56][57] Author contributions Sonja Vaupel: methodology, formal analysis, and writingreview and editing.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond medical applications, these 3D printable hydrogels could also be suitable as enzyme carriers in biocatalysis, as they provide a suitable aqueous microenvironment for the enzyme and the surface is designable via 3D printing. 19,54 Furthermore, these hydrogels could be useful as ion exchangers or absorbers for downstream processing, wastewater treatment, or chromatography. [55][56][57] Author contributions Sonja Vaupel: methodology, formal analysis, and writingreview and editing.…”
Section: Discussionmentioning
confidence: 99%
“…HIAM stands out for its capacity for parallelization, allowing multiple organogels to be printed simultaneously, swelled in distinct solutions, and subsequently calcined/reduced collectively. In Figure 2i Adjuik et al [26] presented an extensive review that delves into the degradability of both bio-based and synthetic hydrogels, with a particular emphasis on their potential as sustainable soil amendments. This comprehensive review explores the environmental implications and ecological consequences of using hydrogels in agriculture, shedding light on the sustainability and compatibility of these materials when applied to soil-enhancement practices.…”
Section: Synthetic Hydrogelsmentioning
confidence: 99%
“…18,19 Recently, it was also reported a novel hydrogel as a reactor packing material produced with a mild 3D printing process. 20 One step further, the functionalities on the 3Dprinted reactor surface can be used for targeted material-biosystem interactions, with enzyme immobilization being the most common approach. 21 Studies have shown that when the biocatalyst is xed in the reactor surface, signicant advantages in terms of stability and reusability arise.…”
Section: D Printing Of Reactors and Reactor Matrices For Flow Biocata...mentioning
confidence: 99%